Contamination, bioaccessibility and human health risk of heavy metals in exposed-lawn soils from 28 urban parks in southern China's largest city, Guangzhou. (April 2016) - Gu, Yang-Guang; Gao, Yan-Peng; Lin, Qin
Abstract: The total concentrations and oral bioaccessibility of heavy metals in surface-exposed lawn soils from 28 urban parks in Guangzhou were investigated, and the health risks posed to humans were evaluated. The descending order of total heavy metal concentrations was Fe > Mn > Pb > Zn > Cu > Cr > Ni > Cd, but Cd showed the highest percentage bioaccessibility (75.96%). Principal component analysis showed that Grouped Cd, Pb, Cr, Ni, Cu and Zn, and grouped Cr and Mn could be controlled two different types of human sources. Whereas, Ni and Fe were controlled by both anthropogenic and natural sources. The carcinogenic risk probabilities for Pb and Cr to children and adults were under the acceptable level (<1 × 10 −4 ). Hazard Quotient value for each metal and Hazard Index values for all metals studied indicated no significant risk of non-carcinogenic effects to children and adults in Guangzhou urban park soils. Highlights: Heavy metals in urban park soils of Guangzhou were investigated. Cd, Pb, Ni, Cu, Zn, and Mn were polluted. Cd showed the highest percentage bioaccessibility. No potential non-carcinogenic risk for children and adults. The carcinogenic risk probability of Pb and Cr were below 1 × 10 −4 .